2019
DOI: 10.22456/1982-8918.86547
|View full text |Cite
|
Sign up to set email alerts
|

El Cuestionamiento Como Herramienta Fundamental Para El Desarrollo De La Toma De Decisiones De Los Alumnos en Educación Física

Abstract: O principal objetivo do estudo foi analisar o efeito de um programa de ensino centrado na compreensão, baseado no questionamento, na tomada de decisões nas ações de passe e do lançamento, numa unidade didática de basquetebol no ensino fundamental. Participaram 37 alunos com idades compreendidas entre 11 e 12 anos. A variável independente foi o programa de intervenção baseado no modelo Teaching Games for Understanding (TGfU). A variável dependente de tomada de decisão foi avaliada através da observação sistemát… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…On the other hand, the application of questioning, as a methodological tool, has probably had a decisive influence on the results obtained, favouring cognitive development (Gréhaigne, Richard & Griffin, 2005) and consequently improving the decision-making (García-González, et al, 2014;Práxedes, et al, 2016a). In line with our results, Gaspar, Del Villar, Práxedes, Moreno (2019) obtained that the students who received the questioning when developing SSG improved their decision-making compared to those who did not.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, the application of questioning, as a methodological tool, has probably had a decisive influence on the results obtained, favouring cognitive development (Gréhaigne, Richard & Griffin, 2005) and consequently improving the decision-making (García-González, et al, 2014;Práxedes, et al, 2016a). In line with our results, Gaspar, Del Villar, Práxedes, Moreno (2019) obtained that the students who received the questioning when developing SSG improved their decision-making compared to those who did not.…”
Section: Discussionsupporting
confidence: 90%
“…If we group the articles, we find that they are usually performed in three large blocks: (a) below 9 lessons; (b) between 12 and 16 lessons; and (c) above 18 lessons, all of them lasting between 40-60 min. In some cases, the total number of lessons includes an initial session and a final session, which serve as pre-and post-TGfU evaluations [38,46]. The first two blocks are where more research is recorded, which is consistent with the fact that all studies, except for Hortigüela-Alcalá and Hernando-Garijo [37] where an implementation was carried out in three consecutive units (24 lessons), were based on a single unit or part of it.…”
Section: Number Of Participants Educational Stage and Durationmentioning
confidence: 68%
“…In addition, we find several studies that compare the results obtained through the application of the TGfU model with other forms of learning, such as: the technical model [34,37], prescriptive feedback [46] or other comprehensive models, such as the Contextualized Sports Literacy Model (CSAM) [35]. They are even compared from a multidisciplinary perspective [57].…”
Section: Purpose and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The review carried out by Barba-Martín et al [50] focused on the Teaching Games for Understanding (TGFU) model and affirmed that the use of this methodology led to the improvement of some specific aspect of the performance and understanding of the game. Some authors confirmed improvements in cognitive development through the implementation of this model [51,52]. Interventions with cognitive components produce significant progress in cognitive functions and tactical skills [37].…”
Section: Discussionmentioning
confidence: 83%